COMPARISON OF EFFICACY OF MILTEFOSINE VERSUS MEGLUMINE ANTIMONATE IN THE TREATMENT OF CUTANEOUS LEISHMANIASIS - Mohammad, Noor; Sagheer, Farah; Majid, Mohammad; khan, Abdul Qayum; Naseem, Sadia; Wasim, Mohammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Cutaneous Leishmaniasis is a morbid condition that generates stigmatization and disfiguring scars. Pakistan is among the ninety-eight countries where cutaneous Leishmaniasis is endemic. Purpose of study was to compare the efficacy of miltefosine and meglumine antimoniate in the treatment of cutaneous Leishmaniasis. Methods: All patients with cutaneous Leishmaniasis (CL) who met the inclusion criteria were divided into two groups using the envelop method. Capsule Miltefosine 50 mg (2.5 mg/ kg) was given to group A, while intralesional Glucantime injection was given to group B. The treatment’s efficacy was evaluated after four weeks and again after eight weeks. Results: Out of 74 patients, 37 patients were included in each group. In group A (miltefosine group), 56.75% were males, and 43.25% were females. In group B (meglumine antimoniate group), 62% were males, while 38% were females (p=0.63). The mean age was 32.81 years±12.09 SD, the mean duration of the disease was 5.4 months±2.3 SD and the mean number of lesions was 2.56±1.33 SD. The efficacy of Miltefosine and meglumine antimoniate (I/L) was 91.9% and 56.75%, respectively (p<0.001). Conclusion: Miltefosine was more effective than intralesional meglumine antimoniate in the treatment of cutaneous Leishmaniasis (p<0.001).